The academy of sciences of the USSR, the library of the academy of sciences of the USSR. . 275 years library of the academy of sciences of the USSR at Leningrad (Biblioteka Akademii Nauk, 1989)
Covertitle: 275 years library of the academy of sciences of the USSR at Leningrad.